2014
DOI: 10.1017/s1368980014002821
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emission of diets in the Netherlands and associations with food, energy and macronutrient intakes

Abstract: Objective: To evaluate the greenhouse gas emission (GHGE) of diets in Dutch girls, boys, women and men and to explore associations with diet composition. Design: Descriptive analyses for the total population as well as stratified for gender, age and dietary environmental load. Setting: The Netherlands. Subjects: Dutch children and adults aged 7-69 years (n 3818). Results: The GHGE of daily diets was on average 3·2 kg CO 2 -equivalents (CO 2 e) for girls, 3·6 kg CO 2 e for boys, 3·7 kg CO 2 e for women and 4·8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
79
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(115 citation statements)
references
References 26 publications
13
79
4
1
Order By: Relevance
“…In contrast, we also show that participants with the largest carbon footprint have an intake of added sugar that is more in line with recommendations. Our finding that the more climate-friendly diet includes more added sugar than the less climatefriendly diet agrees with other studies on the intakes of mono-and disaccharides (8) , total sugars (9) and free sugars (10) . We have not studied which food items the added sugar comes from in the lowest and highest GHGE groups; however, among all participants in the Swedish National Dietary Survey, the main sources of added sugar were sweetened drinks, buns, cookies, cakes, sweets and chocolate (7) .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast, we also show that participants with the largest carbon footprint have an intake of added sugar that is more in line with recommendations. Our finding that the more climate-friendly diet includes more added sugar than the less climatefriendly diet agrees with other studies on the intakes of mono-and disaccharides (8) , total sugars (9) and free sugars (10) . We have not studied which food items the added sugar comes from in the lowest and highest GHGE groups; however, among all participants in the Swedish National Dietary Survey, the main sources of added sugar were sweetened drinks, buns, cookies, cakes, sweets and chocolate (7) .…”
Section: Discussionsupporting
confidence: 92%
“…Temme et al (8) and Scarborough et al (9) found that people with low diet-related GHGE had lower intakes of total fat, SFA and protein, as well as higher intakes of carbohydrates and dietary fibre, compared with people with high GHGE. They reported that the intakes of mono-and disaccharides (8) and total sugars (9) were higher in the group with low compared with high GHGE from food. Vieux et al (10) found that those with the lowest emissions had a higher consumption of free sugars, defined as added sugars and sugars naturally present in honey, syrups and fruit juices.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The strategy of meat substitution has thus been investigated by various authors, but the hypothetical diet scenarios designed were not representative of actual food consumption 5 , 9 , 15 , 16 , 54 . The 5 studies that modeled substitution strategies starting from existing diets are summarized in Table 1 42–45 , 51 and reviewed below. …”
Section: Resultsmentioning
confidence: 99%